User Satisfaction Analysis of Digital Government Services at Health Center: Analisis Kepuasan Pengguna terhadap Layanan Pemerintahan Digital di Pusat Kesehatan - Inayah, Asti Nur; Salim, Marko Ferdian; Santoso, Dian Budi (Procedia of Engineering and Life Science, 2025)
Public health facilities in Bantul Regency have implemented the Digital Government Service (DGS) since 2019 to support healthcare activities. However, its implementation has not been fully optimal, and several challenges remain. User satisfaction is an important indicator of the successful adoption of health information systems. This study aimed to assess user satisfaction with DGS using the End User Computing Satisfaction (EUCS) model across five dimensions: content, accuracy, format, ease of use, and timeliness. A quantitative cross-sectional design was employed with 104 respondents selected through multistage random sampling. Data were collected using questionnaires and observations and analyzed through univariate, bivariate, and multivariate approaches. Most DGS users were female (88%), aged 26–35 years (35%), had diploma-level education (53%), and worked as midwives (24%). Overall, user satisfaction was categorized as “satisfied,” with an average score above 3.401 across the five EUCS dimensions. Regression analysis indicated that all EUCS dimensions had a positive and significant effect on user satisfaction (p < 0.05), and the simultaneous F-test confirmed that all independent variables collectively influenced the dependent variable (p < 2.2e-16). In conclusion, DGS users in Bantul Regency reported a satisfactory level of system use, and all EUCS dimensions were significantly associated with user satisfaction, with independent variables collectively contributing to overall satisfaction.